The Development of Mobility as a Service in China and Its Impact on Automobile Manufacturers - Wong, Hoi Ying (2019)
Mobility as a Service (MaaS) is not only the latest buzzword, but also a driver for the disruptive change in the automotive industry. The aim of this thesis is to suggest new business models for automobile manufacturers so as to capture the opportunities and overcome the threats brought by the development of MaaS. To begin with, the author first analyses the current situation of the Chinese MaaS market based on three different levels: country level, industry level, and customer level. Secondary research and customer survey are adopted to collect data for the analytical purpose. Thereafter, expert interviews are conducted in order to generate insights into the possible new business model options. Based on all the findings, three new business model options, which are B2B asset provider, Mobility service provider, and Autonomous mobility experience pioneer are proposed by using the 4I framework for the innovation process.